Apoio governamental à inovação tecnológica: análise da indústria farmacêutica paraense - Oliveira, Gabriel Antônio Ribeiro (2010)
The transformations economical, cultural and social that happen in world ambit they are associated to the intense progress and expansion of new technologies, forcing governments, people, companies and nations to the introduction of new patterns of behavior, forcing, in that way, to the continuous renewal of products and technological processes to maintain the competitiveness, so much among nations, as in the managerial world. In that matter, the technological innovation is recognized as basic factor of maintainable economical competitiveness, being the responsible for the breaking and/or improvement of the techniques and production processes, what presupposes the systematization varied institutional arrangements that they involve firms, interaction nets among companies, government agencies, universities, research institutes, laboratories of companies and scientists and engineers activities. Those arrangements, to the if they articulate with the educational system, with the industrial and managerial section and, also, with the financial institutions, they take the form that Freeman (1987) it coined of national system of innovation, promoted through public politics of CT&I, which seek to induce and to support innovative initiatives in the companies, as well as to establish demands and to prioritize vocations and regional potentialities. In that context of government support to the technological innovation interferes this study, that it looked for to know the reasons of the fragility innovative in the pharmaceutical industry of State of Pará in Brazil, pointed for PINTEC (2005), starting from the point of view of the businessmen of that section. For such, the qualitative approach was used - with interviews directing semi and the technique of the content analysis. The results of the research pointed that the fragilities innovative of the section links to the ignorance of the government support to the technological innovation on the part of the businessmen of the pharmaceutical industry of State of Pará in Brazil